Aspirin for the Primary Prevention of Cardiovascular Disease: A Review of the Literature and Considerations for Clinical Practice. Issue 2 (March 2020) - Cicci, Jonathan D.; Iyer, Prashanth; Clarke, Megan M.; Mazzella, Anthony J.
Abstract : Cardiovascular disease is the leading cause of death globally, and deaths due to coronary heart disease or stroke account for over half of all cardiovascular deaths in the United States. While many important advances have been made in the treatment and secondary prevention of atherosclerotic cardiovascular disease (ASCVD), morbidity and mortality remain high. Aspirin has been commonly used for the primary and secondary prevention of ASCVD for decades and is an easily accessible therapeutic option. While it is a cornerstone of secondary prevention, its role in primary prevention is less clear and professional guidelines have differed in their recommendations. As literature has substantially evolved over the past 40 years, so too has our understanding of aspirin's role in the primary prevention of ASCVD. This article reviews landmark clinical trials of aspirin in primary prevention and highlights key changes in dosing strategies and demographics.